2015
DOI: 10.1016/j.fob.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid regulates a key redox control factor Nrf2 via phosphorylation of Akt in bovine articular chondrocytes

Abstract: HighlightsHyaluronic acid (HA) has a pharmacological role for reduction of cellular superoxide.In HA-treated chondrocytes, expression of Nrf2 and its downstream genes was upregulated.Inhibition of Akt or suppression of HA receptors prevented HA-mediated Nrf2 accumulation.Nrf2 siRNA inhibited the HA effect on antioxidant enzymes.HA might contribute to ROS reduction through Nrf2 regulation by activating Akt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 50 publications
(59 reference statements)
3
40
0
Order By: Relevance
“…Numerous studies have confirmed the effect of HA on the activity of these enzymes but in other cells and tissues and not in erythrocytes [75,76]. It was confirmed that HA can reduce cellular superoxide generation and its accumulation through Nrf2 regulation which can induce transcription of antioxidant enzymes such as SOD, GPx, CAT, and others [61]. Supplementary to its primary role in cytoprotection, Nrf2 is also linked to differentiation, proliferation, growth, and apoptosis, and it is thought that Nrf2 has evolved from an original role in hematopoiesis and the regulation of cell differentiation from early lineages [77].…”
Section: Evaluation Of Results Of Administration Of Hyaluronans In Exmentioning
confidence: 98%
See 1 more Smart Citation
“…Numerous studies have confirmed the effect of HA on the activity of these enzymes but in other cells and tissues and not in erythrocytes [75,76]. It was confirmed that HA can reduce cellular superoxide generation and its accumulation through Nrf2 regulation which can induce transcription of antioxidant enzymes such as SOD, GPx, CAT, and others [61]. Supplementary to its primary role in cytoprotection, Nrf2 is also linked to differentiation, proliferation, growth, and apoptosis, and it is thought that Nrf2 has evolved from an original role in hematopoiesis and the regulation of cell differentiation from early lineages [77].…”
Section: Evaluation Of Results Of Administration Of Hyaluronans In Exmentioning
confidence: 98%
“…One important pharmacological function of HA is the reduction of cellular superoxide generation and accumulation through nuclear factor erythroid 2-related factor 2 (Nrf2) regulation, which is a master transcription factor in cellular redox reactions. Antioxidants and phase II detoxifying enzymes such as catalase (CAT), superoxide dismutase (SOD), heme oxygenase-1, glutathione S-transferase, glutathione peroxidase (GPx), and thioredoxin are coordinated at transcription level by Nrf2, so the hyaluronic acid could affect the activity and quantity of these antioxidant enzymes (Figure 7) [61].…”
Section: Hyaluronan In Arthritis: Regulation Of Inflammation Through mentioning
confidence: 99%
“…It is known that increased adhesion by FN-integrin β1 interaction plays an essential role in regulating cell proliferation, survival, and migration by triggering several signaling pathways (Leiss et al 2008, Schmidt & Friedl 2010, Schiller et al 2013, Nakagawa et al 2014, especially PI-3K-Akt pathway, which is the most important pathway to promote cell survival (Benbrook & Masamha 2011). Interaction of CD44 with its ligands, including FN, can also enhance proliferation, survival, and invasion by activating PI-3K-Akt pathways (Li et al 2015, McFarlane et al 2015, Onodera et al 2015. In this study, we demonstrated that DEX could enhance the activation of Akt, which is a late phase and sustained regulation, suggesting that Akt activation is not a direct effect of DEX, but the result of DEXenhanced cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of FN-integrin β1 or FN-CD44 mediates the cell adhesion, and induces signaling, such as activating PI-3K-Akt pathway (Schmidt & Friedl 2010, Nakagawa et al 2014, Li et al 2015, Onodera et al 2015, McFarlane et al 2015, which is an important pathway to promote cell survival (Benbrook & Masamha 2011). We then examined whether PI-3K-Akt pathway was involved in the prosurvival effect of DEX in ovarian cancer cells.…”
Section: Activation Of Akt Pathway Is Involved In Pro-survival Effectmentioning
confidence: 99%
“…The major structural component of brain extracellular matrix (ECM) is hyaluronan (HA), which not only serves as the main anchoring point for brain cells but is also an important facilitator of intracellular signaling. CD44 and RHAMM are primary receptors for HA that signal to AKT upon binding (Lin, Chang, & Ying, 2007;Onodera, Teramura, Takehara, & Fukuda, 2015;Trapasso & Allegra, 2012, p. 44…”
Section: Ha-akt Signalingmentioning
confidence: 99%